Reconstruction of Interculturality-Based Arabic Language Pedagogy to Bridge Islamic Civilization and the Global World - Fahraini, Sovia; Hilmy, M. Insan; Firdaus, Ahmad Yanif (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study is motivated by the importance of the Arabic language as a language of religion, science, and global communication in the Muslim world, whose teaching practices still tend to focus on grammatical and textual aspects while lacking the incorporation of intercultural dimensions. This condition has led to a low level of students’ contextual communicative competence in responding to global realities. The research problems include: how the concept of interculturality-based Arabic language pedagogy is formulated, how its instructional reconstruction is carried out, and what its implications are in bridging Islamic civilization and the global world. This study employs a qualitative approach using the library research method, with content analysis, comparative analysis, and conceptual synthesis of relevant literature. The findings reveal that interculturality-based Arabic language pedagogy emphasizes the integration of linguistic aspects, Arab culture, and global culture, as well as the strengthening of intercultural communicative competence through dialogue between Islamic values and contemporary global issues. The pedagogical reconstruction is carried out through the reorientation of objectives, the development of integrative materials, dialogic strategies, and the role of the teacher as a cultural facilitator. This study contributes by offering a conceptual model of Arabic language pedagogy that is adaptive, integrative, and relevant for curriculum development and instructional practices in the global era.